Teaching epidemiology and biostatistics: A peer-led teaching module for postgraduate psychiatry student - Pang, Nicholas Tze Ping; Eugene Koh; James, Sandi; Mohd Amiruddin Mohd Kassim (Penerbit UMS, 2022)
Background and Objective: Biostatistics and epidemiology have been integral subjects in any postgraduate courses, including medical specialties Master programs. Both are widely accepted as among the difficult and confusing subjects, which worsen by lack of adequate exposure and often, time constraints. Hence, peer-led learning approach was proposed as a viable option to the traditional lecturer-driven learning style. Method: The peer-led approach intends to promote targeted learning and conceptual understanding, instead of widely sweeping learning, which is rather directionless and could cause information overload. Discussion: Students were divided into two groups, namely humanities-inclined group and science-inclined group. Different pedagogical methods to address the different groups were discussed. Conclusion: This approach helps to make the learning more palatable, boosting knowledge retention and fostering camaraderie spirit among colleagues.